Can work-to-family conflict lead to preschool children’s social behavior problems?—The chain mediating roles of guilt about parenting and parent-child relationships - Wang, Yan; Shi, Dasheng; Liu, Guolei; Zhang, Mengmeng; Zheng, Xinhong (Frontiers in Psychology, 2023)
Parents’ work-to-family conflict has been reported to be associated with preschool children’s social behavior problems, but the underlying mechanisms of this association in the Chinese cultural context remain unclear. Based on ecosystem theory and the spillover-crossover model theory of emotion, this study aimed to examine the correlation between parents’ work-to-family conflict and preschool children’s social behavior problems in China, as well as the mediating role of guilt about parenting and parent–child relationships. Structural equation modeling was used to check the research hypotheses with a sample of 3,038 parents of Chinese preschool children. The main findings of this study are as follows: (1) Work-to-family conflict faced by parents was positively associated with guilt about parenting and preschool children’s social behavior problems; (2) The effect of guilt about parenting on preschool children’s social behavior problems was bidirectional; guilt about parenting was positively related to preschool children’s social behavior problems, but when guilt about parenting prompted parents to adjust their parent–child relationships, it was negatively related to preschool children’s social behavior problems. Taken together, these results further explain the interaction between parents’ work-to-family conflict and preschool children’s social behavior problems and discuss the influence of multiple factors on preschool children’s social behavior problems. Theoretically, this study enriches the theoretical basis of the interaction with resources from the external environment of home education and family education. Practically, it implies that multiple levels, such as the government, early childhood education institutions, and work units, should give more support to preschool children’s family education and thus work together to promote the healthy development of preschool children.